Misbelief : what makes rational people believe irrational things - Ariely, Dan (HarperCollins, 2023)
"Misinformation affects all of us on a daily basis--from social media to larger political challenges, from casual conversations in supermarkets, to even our closest relationships. While we recognize the dangers that misinformation poses, the problem is complex--far beyond what policing social media alone can achieve--and too often our limited solutions are shaped by partisan politics and individual interpretations of truth. In Misbelief, preeminent social scientist Dan Ariely argues that to understand the irrational appeal of misinformation, we must first understand the behavior of "misbelief"--the psychological and social journey that leads people to mistrust accepted truths, entertain alternative facts, and even embrace full-blown conspiracy theories. Misinformation, it turns out, appeals to something innate in all of us--on the right and the left--and it is only by understanding this psychology that we can blunt its effects. Grounded in years of study as well as Ariely's own experience as a target of disinformation, Misbelief is an eye-opening and comprehensive analysis of the psychological drivers that cause otherwise rational people to adopt deeply irrational beliefs. Utilizing the latest research, Ariely reveals the key elements--emotional, cognitive, personality, and social--that drive people down the funnel of false information and mistrust, showing how under the right circumstances, anyone can become a misbeliever. Yet Ariely also offers hope. Even as advanced artificial intelligence has become capable of generating convincing fake news stories at an unprecedented scale, he shows that awareness of these forces fueling misbelief make us, as individuals and as a society, more resilient to its allure. Combating misbelief requires a strategy rooted not in conflict, but in empathy. The sooner we recognize that misbelief is above all else a human problem, the sooner we can become the solution ourselves."